To see the Gross Qualitative Parameters such as General Appearance of Rats and their testes after Long and Short Term Use of Sildenafil Citrate (Medical Forum Monthly, 2024)
Objective: To see the gross qualitative parameters such as general appearance of rats and their testes after long and short term use of Sildenafil Citrate.Background: As very little attention has been given to explore the effects of a sildenafil citrate on histological aspects of testes, hence this experimental study was designed to check whether the drug which is being used indiscriminately in our country and abroad is safe or it has any harmful effect on the architecture of rat testis.Study design: Experimental StudyPlace and Duration of Study: This study was conducted in departments of Anatomy & Histopathology Shaikh Zayed Hospital Lahore for a period of six weeks from 02.05.2008 to 17.06.2008.Materials and Methods: Sample size consisted of 45 animals, divided into Group A (Control), Group B and C (Experimental), Each group was consisting of 15 animals. Physical examination of rats and their testis was done every day by the author himself and recorded.Results: After giving drug, on inspection of rats all the animals were active and healthy and the gross appearance of the testes was normal except in an animal, in which the testes were smaller than the associates of the same group. Eating habits of all the animals were normal, taking food and water freely. After half an hour of giving the drug, they were mounting over each other and looked aggressive. The comparison of all the groups, A vs B, A vs C and B vs C remained statistically non –significant (P>0.05).Conclusion: No significant difference was observed in qualitative parameters (general appearance) of the rats and their testes after giving sildenafil citrate.